2018
DOI: 10.1002/hbm.24225
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in glutamate + glutamine levels of healthy young adults assessed by proton magnetic resonance spectroscopy

Abstract: The glutamatergic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor is involved in synaptic plasticity processes, and animal studies have demonstrated altered expression across the sleep wake cycle. Accordingly, glutamate levels are reduced during non-rapid eye movement (NREM) sleep and the rate of this decrease is positively correlated with sleep EEG slow wave activity (SWA). Here, we combined proton magnetic resonance spectroscopy ( H-MRS) and high-density sleep EEG to assess if H-MRS is s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…These results can be attributed to increased energy demands and increased need for removal of metabolic waste products from the brain during sleep deprivation (Xie et al., ). Diurnal changes in brain glutamate and glutamine levels were recently observed in healthy young adults with a significant overnight reduction assessed by proton magnetic resonance spectroscopy (Volk, Jaramillo, Merki, O'Gorman Tuura, & Huber, ). In addition, a previous study reported reduced glutamine levels associated with lower total sleep time and increased wake‐time after sleep onset (Miller et al., ), supporting our hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…These results can be attributed to increased energy demands and increased need for removal of metabolic waste products from the brain during sleep deprivation (Xie et al., ). Diurnal changes in brain glutamate and glutamine levels were recently observed in healthy young adults with a significant overnight reduction assessed by proton magnetic resonance spectroscopy (Volk, Jaramillo, Merki, O'Gorman Tuura, & Huber, ). In addition, a previous study reported reduced glutamine levels associated with lower total sleep time and increased wake‐time after sleep onset (Miller et al., ), supporting our hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Methodological advances in 1 H-MRS have recently permitted the noninvasive detection of naturally occurring changes in tightly regulated metabolite concentrations in circumscribed areas of the human brain. Whereas one recent study suggested that GLX levels in the left parietal lobe decrease overnight [45], previous data from this lab revealed no significant changes after sleep deprivation in GLX/Glu and GABA in the medial prefrontal cortex [17]. Thus, the exact roles in humans of the main excitatory and inhibitory neurotransmitters in circadian and homeostatic sleep–wake regulation remain unclear.…”
Section: Resultsmentioning
confidence: 95%
“…Structures such as medial the temporal lobe, prefrontal cortex, and posterior cingulate cortex are prone to diurnal fluctuations at the neuronal activity level . At the metabolic level, diurnal variations of major metabolites such as NAA, tCr, Glx, and GABA have been previously investigated using single‐voxel spectroscopic methods, with mixed outcomes. Soreni et al in 2006 found a statistically significant increase in NAA but not with creatine levels on the striatum in the morning .…”
Section: Discussionmentioning
confidence: 99%
“…Soreni et al found significantly higher levels of NAA during afternoon sessions in a group of healthy controls, which they claim is due to possible changes in circadian mediators such as temperature, hydration, and osmotic regulation . In contrast, Volk et al observed a significant overnight reduction in Glx, whereas other metabolites were not affected by the circadian change . Other studies, on the other hand, showed that the time of day had no bearing on metabolic concentrations, in particular, GABA and other major metabolites such as NAA and creatine .…”
mentioning
confidence: 97%